(untitled) - Murray R Spiegel (New York, 1994)
The book covers the algebra ang geometry og complex numbers, complex differential and integral calculus, infinite series including Taylor and Laurent series, the theory of residues with applications drawn from various fiels. Each chapter begins with a clear statement of pertinent definitions, principles and theorems together with illustrative and other descriptive material
Giải tích phức
Keywords: functions of complex variables